Защитные экраны и поглотители электромагнитных волн - Островский, О. С.; Одаренко, Е. Н.; Шматько, А. А. (ХНУ імені В.Н. Каразіна, 2003)
Basic principles of different object protection from the microwave radiation effect on the base of shielding and using the radioabsorb materials are considered. This work is devoted to review of different types of shields, design and materials for their fabrications. Electromagnetic characteristics of radioabsorb materials and media, including composite and chiral, and physical principles of their operation are considered.
Keywords: поглотитель; электромагнитная волна; защитный экран